The Dual Regulatory Challenge: What is CE Marking for AI Medical Devices? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The rapid integration of Artificial Intelligence AI into healthcare is transforming diagnostics, treatment planning, and patient monitoring. As AI-powered me...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care